The Repayment of Unsecured Debt by European Households. (20th October 2016) - Grant, Charles; Padula, Mario
Summary: The existing literature that estimates the incidence of arrears relies on either household survey data or administrative data derived from the lender's records of their borrowers. But estimates based on these different sources will give different estimates of arrears. Moreover, the estimates are not useful for policy analysis or for a bank's lending decision, since they ignore the fact that some households do not borrow. The paper discusses the selection issues that are involved in using either source of data and is the first paper to bound the estimate of the household's underlying propensity to repay. To demonstrate the methodology, it uses data from the European Union Survey of Income and Living Conditions survey for 2008 to estimate the factors that affect repayment among Eurozone households.